Mercury uptake by Zea mays L. grown on an inceptisol polluted by amalgamation and cyanidation tailings of small-scale gold mining - Yusrin Afandi; R Sri Tejowulan; Baiq Dewi Krisnayanti (Journal of Degraded and Mining Lands Management, 2019)
Pollution of agricultural land by tailings from the Artisanal and Small-Scale Gold Mining (ASGM) can increase the concentration of mercury (Hg) in plant tissue thus; it will endanger the health of humans and animals that consume it. This study aimed to determine the amount of Hg taken up by maize plants on an inceptisol contaminated with tailings from amalgamation and cyanidation processes of small-scale gold mining. A field experiment was conducted at the experimental field of Faculty of Agriculture, University of Mataram by using a factorial randomized block design consisting of two factors, namely: (1) tailings (L), and (2) ) fertilization (N). The results indicated that adding amalgamation and cyanidation tailings increased the physical and chemical fertility of the soil studied but caused Hg pollution. Most of the Hg in plant tissue was concentrated in the roots of the plants. The content of Hg in the plant shoot was above the threshold value of mercury allowed in plants. The NK33 variety of maize can be categorized as a mercury tolerant plant as the plant grew well in a mercury-contaminated soil.